Effects of Classroom Composition on the Development of Antisocial Behavior in Lower Secondary School. (18th February 2015) - Müller, Christoph Michael; Hofmann, Verena; Fleischli, Janine; Studer, Felix
Abstract : Early adolescence is a critical period during which classroom composition may affect behavioral development. This study investigated whether classmates' levels of aggression and delinquency influenced individual antisocial behavior during the first year of secondary school. At this point, students had just transitioned to a new classroom peer environment. A short‐term longitudinal design with four measurement points distributed across the school year was applied. Data were collected from the anonymous self‐reports of 825 seventh graders. Longitudinal negative binomial multilevel analyses revealed that classmates' antisocial behavior influenced pupils' behavioral development (other peer influences were controlled). Furthermore, classroom behavioral heterogeneity moderated the peer effect regarding delinquency but not aggression.